Are We Rational or Not? The Exploration of Voter Choices during the 2016 Presidential and Legislative Elections in Taiwan - Lee, I-Ching; Chen, Eva E.; Yen, Nai-Shing; Tsai, Chia-Hung; Cheng, Hsu-Po (Frontiers in Psychology, 2017)
The decisions voters make—and whether those decisions are rational—have profound implications on the functionality of a democratic society. In this study, we delineated two criteria in evaluating voter rationality and weigh evidence of voter rationality versus irrationality. Furthermore, we compared models in two different elections in Taiwan to explore the reasons behind the irrational choices voters can make. Survey questions and an implicit association test were administered prior to both elections among 197 voters in Taipei. These voters then reported their actual votes post-election. Model testing suggests that voters often are rational, but are more likely to make irrational choices in more important elections. Our findings indicate that voters generally aim to be diligent and to optimize their choices, even if they make less rational choices in the end. Further implications regarding elections and human rationality are discussed.